1939
DOI: 10.1242/jeb.16.3.251
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Drugs, Especially Acetylcholine, on the Annelid Body Wall (Lumbricus, Arenicola)

Abstract: 1. The actions of certain drugs (acetylcholine, eserine, atropine, nicotine, adrenaline) on strips of the body wall of the earthworm (Lumbricus terrestris) and lugworm (Arenicola marina) are described. 2. The body wall of the earthworm and lugworm resembles the dorsum of the leech, and also vertebrate skeletal muscle, in the following points: relatively insensitive to acetylcholine alone, sensitivity to acetylcholine greatly increased by eserine, response to acetylcholine abolished by nicotine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1941
1941
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An investigation of the muscular responses of the earthworm body wall is of especial interest since this muscle seems to parallel vertebrate striated muscle in some of its physiological characteristics. Certain of these similarities have been referred to by Pantin (1935b) and by Wu (1939).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…An investigation of the muscular responses of the earthworm body wall is of especial interest since this muscle seems to parallel vertebrate striated muscle in some of its physiological characteristics. Certain of these similarities have been referred to by Pantin (1935b) and by Wu (1939).…”
Section: Introductionmentioning
confidence: 86%
“…worm body wall muscles, application of physostigmine was tried. Wu (1939) has shown that the sensitivity of the body wall to acetylcholine is greatly increased by physostigmine. From the results of his experiments concerning the action of drugs on the earthworm body wall, he postulated the presence of some factor which prevented the action of acetylcholine and which was antagonized by physostigmine.…”
Section: Augmented Responsesmentioning
confidence: 99%